Isolation and screening of chitosanase producing microorganisms - Wangtueai, Sutee; Worawattanamateekul, Wanchai; Sangjindavong, Mathana; Naranong, Nuanphan; Sirisansaneeyakul, Sarote (My University, 2006)
A total of 183 isolates of microorganisms were collected from forest soil with the shrimp wastes deposited. The selected four bacterial isolates with high activity of chitosanolytic enzymes on chitosanase detected agar plates (CDA-plates) were TP11.03, TP11.22, TP12.24 and KU22.13. Among them, the potential isolate TP12.24 was identified as Bacillus cereus which produced the highest amount of chitosanase on M9-Chitosan medium.
Keywords: Bacillus cereus; Chitosan; Chitosanase; Isolation